Sigillum Sacramentale: Rahasia Sakramental Pengakuan Dosa. Studi Kanonik - Daniel Ortega Galed (Studia Philosophica et Theologica, 2023)
One of the special graces possessed by a priest is the authority to act in persona Christi capitis when granting absolution for the sins of the penitent. They received this authority from Christ himself, the only One who could forgive human sins. However, that grace also brings a great duty. They are bound by a divine obligation to keep the seal of confession. This canonical study will describe how the concept of the sigillum sacramentale or the inviolable sacramental seal of confession is developed in canon law. It will also explain what is meant by divulging the seal of confession directly and indirectly. From the perspective of the Penal Code of Canon law, it will also discuss canonical sanctions for priests who violate them and how the punishments will be revoked. Finally, this study is expected to foster seriousness and responsibility for priests in serving the Sacrament of Penance, the sacrament that reconciles humans with God.